(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
This discussion paper explores the current drivers of change in Higher Education institutions in England. It presents models of students and asks you to consider your own institution and student engagement within it. It will then offer detail of a current research project that Newman University have begun.